Perancangan Interior Lego House sebagai Pusat Edukasi dan Retail di Surabaya - Ade Ulfa Apriliana; Cok Gede Padmanaba; Sherly de Yong (Intra, 2016)
Education is the most important things for children. Education can be applied in various ways such as learning by playing with educational toys. Currently, there are only a few play area for children at the mall, so it is necessary to create one area that can comply the problems. Some of the existing play areas in Surabaya, especially in malls, still don’t have an educational value in it. It is necessary to have an educational value in a play area for children. Lego is one of an educative toys for kids and also a well-known toy brands, known by almost everyone ranging from kids to adults, like Lego House. Besides that, a store is needed to complete this Lego House design. The design method used are design thinking and mind mapping. There are 4 stages in this method which are, observation (this is the stage of collecting data and information about education and lego), brainstorming (this is the stage of a problem solving with concept, mind mapping, and some sketch), prototyping (this is the stage of creating a mock up), and implementation (this is the stage of making the final design). The result of those problem solving are the concept of “play lego on the street” where there’s an educational value in it. The meaning of word “play” is playing, and playing can bring out the educational value with educative toys like lego. This concept has its own characteristic in its interior because of the street themes to attract the children.